(untitled) (Balneo and PRM Research Journal, 2024)
ABSTRACT Background: Remaining phenomena presented by people who endured COVID -19 at various times after the acute phase of the disease, remain the objectives of the medical and social approaches. Musculoskeletal pain is increasingly reported by patients as one of the persistent symptoms in post-COVID-19 syndrome. The purpose of the study was the qualitative and quantitative assessment of musculoskeletal pain post _COVID 19 in the process of in-hospital medical rehabilitation. Methods: A group of 124 people who suffered SARS-Cov-2 infection were analyzed and underwent rehabilitation treatment with physiotherapy, halotherapy and electrotherapy sessions in the specialized “Post COVID rehabilitation” ward during a period of 14 days. For the analysis of the pain phenomenon, 103 people who presented musculoskeletal pain, before and after treatment were assessed by the Nordic Musculoskeletal Questionnaire, pain intensity by VAS scale and intensity of fatigue syndrome. Results. Musculoskeletal pain was present in 84.3% of cases among persons admitted for rehabilitation treatment. Rehabilitation programs applied under inpatient conditions increased the rate of people with moderate and mild pain by 6.8% and decreased the rate of those with severe pain by 13.6% (p< 0.05), assessed by the Nordic Musculoskeletal Questionnaire. The proportion of patients with severe pain, assessed by the VAS scale, decreased by 13.8% at discharge from the hospital. Conclusion. In-hospital medical rehabilitation programs applied to people with musculoskeletal pain post -COVID 19 had a beneficial effect by decreasing the number of painful areas and pain intensity. Keywords: post-COVID medical rehabilitation, musculoskeletal pain